Optical-transmission based water turbidity measurement system - Ahmad Shauri, Ruhizan Liza; Wagiran, Rahman; Mohd Noor, Samsul Bahari; Mohd Sidek, Roslina; Abdullah, Abdul Ghani Liew (Federation of Engineering Institutions of Islamic Countries, 2006)
An optical-transmission based system for measuring water turbidity was developed. A silicon PIN photodiode BPX65 was used for this application due to its high photosensitivity in the range of 350 nm to 1100nm. The results obtained show that the proposed turbidity measurement system gave a linear relationship between the input and the output signal of the system. Based on the random data obtained, the results given by the proposed system was comparable with the commercial turbidimeter.